(untitled) (Al-Aasar, 2026)
This study investigates the linguistic strategies employed in Pakistani English newspaper editorials to represent the Palestine issue, with specific reference to Dawn and The News during the period 2024–2025. Grounded in Norman Fairclough’s Three-Dimensional Model of Critical Discourse Analysis (CDA), the research examines how language operates at textual, discursive, and social levels to construct political meanings, reflect ideological positions, and influence public opinion. At the textual level, the study analyses lexico-grammatical features such as evaluative vocabulary, transitivity patterns, modality, and rhetorical devices. At the discursive practice level, it explores processes of intertextuality, sourcing, and framing, while the social practice dimension situates the editorials within broader geopolitical, ideological, and power structures. Adopting a qualitative research design, twelve editorials are purposively selected based on their explicit focus on the Palestine issue and analyzed in detail to uncover recurring discursive patterns. The findings reveal that both newspapers consistently foreground Palestinian suffering, construct Israel as an active agent responsible for violence, and employ moral and legal discourses to challenge dominant Western media representations of the conflict. Rather than presenting the issue as a neutral geopolitical struggle, the editorials frame it as a humanitarian and ethical crisis rooted in systemic injustice. The study concludes that Pakistani English newspaper editorials are ideologically charged texts that play a crucial role in reproducing power relations, resisting hegemonic narratives, and shaping readers’ political consciousness regarding the Palestine issue.